Simulating City-Bus On-Road Operation With VECTO - Zacharof, Nikiforos; Özener, Orkun; Özkan, Muammer; Kilicaslan, Abdullah; Fontaras, Georgios (Frontiers in Mechanical Engineering, 2019)
Heavy-duty vehicles constitute a significant contributor to road CO2 emissions, despite accounting for only a low share of the vehicle fleet. CO2 Emissions certification and monitoring are performed using vehicle simulation software designed for the purpose (VECTO). The European Union currently regulates rigid truck and tractor-trailer CO2 emissions and subsequently will proceed to buses and other heavy-duty vehicle categories. The current study investigated the use of VECTO on a city bus by modelling the on-road operating conditions of a vehicle in an urban route in Istanbul. The simulation results showed a difference with the on-road measurements in the range of -1.6% to 3.2%, depending on the direction of the route. The difference was attributed to the influence of the total elevation change, and the use of auxiliaries. The latter comprise a significant part of energy consumption in buses, and for this reason, VECTO includes a dedicated bus auxiliary module. The use of the module was also explored, and it was found to improve the results in some cases. The findings highlight the need to assess the operation of auxiliary components in city buses accurately, and to consider the provision of more precise, auxiliary-component specific, information when running actual real-world CO2 simulations of these vehicles.